ESSENTIALS OF MANAGEMENT - KOONTZ HAROLD (CHENNAI MCGRAW HILL EDUCATION INDIA PRIVATE LIMITED, 2024)
"Essentials of Management" by Harold Koontz and Heinz Weihrich is a foundational textbook that has been a cornerstone of management education for decades. It provides a comprehensive overview of the fundamental principles and functions of management. Later editions have been updated by Mark V. Cannice to maintain relevance in the contemporary business environment.
MANAGEMENT
BBA & MBA
Keywords: MANAGEMENT